PENGARUH KEDISIPLINAN, BUDAYA ORGANISASI DAN KOMPETENSI PEGAWAI TERHADAP TINGKAT KEPUASAN PIMPINAN PADA STASIUN KARANTINA PERTANIAN KELAS I TANJUNGBALAI ASAHAN - Hendra Bangsawan Daulay; Bahrumsyah Putra; Syariah .; Rahma Ayuni; Nafisah . (Manajemen dan Bisnis, 2021)
The   formulation   of   the   problem   in   this   study   are:   How   do   discipline, organizational   culture   and   competence   influence   the   level   of   leadership satisfaction.  This study aims to examine  how discipline,  organizational  culture and competence influence the level of leadership satisfaction. With total sampling technique,  the sample in this study amounted  to 51 people. Discipline  variable partially   has   a   positive   effect   on   the   level   of   leadership   satisfaction; Organizational  culture variables  partially  have a positive  effect on the level of leadership satisfaction; Employee competency variables partially have a positive effect on the level of leadership satisfaction; Discipline variables, organizational culture and employee competence simultaneously have a positive and significant effect on the level of leadership satisfaction